Bouncing Back! Counteracting Muscle Aging With Plyometric Muscle Loading - Franchi, Martino V.; Monti, Elena; Carter, Austin; Quinlan, Jonathan I.; Herrod, Philip J. J.; Reeves, Neil D.; Narici, Marco V. (Frontiers in Physiology, 2019)
Abstract The preservation of muscle power is crucial in ageing for maintaining mobility and performing daily tasks. Resistance training involving high movement velocities represents a valid strategy to slow down the rate of sarcopenia, counteracting the loss of muscle mass and muscle power. Plyometric exercise may represent an effective training modality for increasing muscle power; however, its application in older populations has been sparingly investigated, as the high impact actions involved may reduce its feasibility for older individuals. By adopting a safer modality of plyometric training, we investigated if a 6-week plyometric training intervention could increase knee extensor muscle size, architecture, force and power in fourteen young (YM, age = 25.4 ± 3.5 y; means ± SD) and nine older males (OM, age = 69.7 ± 3.4 y). Volunteers trained 3 times/week using a device similar to a leg press machine where the user was required to bounce against his body mass on a trampoline. Pre-to-post training changes in isometric maximum voluntary torque (MVT), leg extension power and vastus lateralis (VL) architecture were assessed. Muscle power increased in both groups (+27% OM -P<0.001, 20% YM -P<0.001), although the total external work performed during the training period was significantly lower for OM (i.e., -47%). Both groups showed significant increases in muscle thickness (MT) (+5.8 OM -P<0.01 vs. +3.8% YM -P<0.01), fascicle length (Lf) (+8% OM -P<0.001 vs. +6% YM -P<0.001), and pennation angle (PA) (+7.5% OM -P<0.001 vs. +4.1% YM -P<0.001). The current study shows that trampoline-based plyometric training is an effective intervention producing a rapid increase in muscle mass and power in both young and older individuals. The training modality used in this study seems to particularly benefit the older population, targeting the morphological and functional effects of sarcopenia in human muscle.